TRANSLATION SHIFTS AND THE EQUIVALENCE IN TRANSLATION - Filimonova, Liliya (Журнал иностранных языков и лингвистики, 2023)
Tashkent State Transport University started new direction on preparation of the experts in transport sphere translation. This will give us confidence in exchange of experience and documents arrangement between Uzbekistan and foreign countries, where Uzbekistan is going to send its goods by freight trains and automobile road trucks.